MCCANN AND OTHERS V. THE UNITED KINGDOM - A PRECEDENT ON THE ESTABLISHMENT OF POSITIVE OBLIGATIONS REGARDING THE PLANNING AND CONTROL OF OPERATIONS OF LAW ENFORCEMENT OFFICIALS IN ACCORDANCE WITH ART.2 ECHR - Martinov, Darija (Glasnik Advokatske komore Vojvodine, 2021)
Positive obligations are obligations of the Member States of the European Convention for the Protection of Human Rights and Fundamental Freedoms to take active steps to protect the rights guaranteed by this Convention. When it comes to the protection of the right to life, as one of the basic human rights, the case of McCann and others c. the United Kingdom set a precedent and established new obligations for States parties to the Convention when it comes to planning and conducting law enforcement operations. The manner in which these obligations were established, their scope and content, as well as the comments of legal theory and practicians on this innovative judgment, are the subject of the analysis of this paper.